2003
DOI: 10.1093/nar/gkg637
|View full text |Cite
|
Sign up to set email alerts
|

Lack of sugar discrimination by human Pol   requires a single glycine residue

Abstract: DNA polymerase mu (Pol mu) is a novel family X DNA polymerase that has been suggested to play a role in micro-homology mediated joining and repair of double strand breaks. We show here that human Pol mu is not able to discriminate against the 2'-OH group of the sugar moiety. It inserts rNTPs with an efficiency that is <10-fold lower than that of dNTPs, in sharp contrast with the >1000-fold discrimination characteristic of most DNA-dependent DNA polymerases. The lack of sugar discrimination by Pol mu is demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
120
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 31 publications
13
120
2
Order By: Relevance
“…6 Thus, the duplex hybrid nucleic acid would be structurally altered, having both A-and B-like qualities (48), relative to that normally encountered by pol ␤ and thereby interfering with proper binding. Similarly, catalytic efficiency of pol was severely diminished on substrates containing either a complete RNA primer or template (27,49). Consequently, although one or two ribonucleotide(s) in the upstream primer is(are) tolerated by X-family DNA polymerases, a stretch of ribonucleotides is expected to interfere with nucleic acid binding and DNA synthesis.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…6 Thus, the duplex hybrid nucleic acid would be structurally altered, having both A-and B-like qualities (48), relative to that normally encountered by pol ␤ and thereby interfering with proper binding. Similarly, catalytic efficiency of pol was severely diminished on substrates containing either a complete RNA primer or template (27,49). Consequently, although one or two ribonucleotide(s) in the upstream primer is(are) tolerated by X-family DNA polymerases, a stretch of ribonucleotides is expected to interfere with nucleic acid binding and DNA synthesis.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Early studies (reviewed in (1,2)) revealed that DNA polymerases do incorporate rNMPs during DNA synthesis. Kinetic studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) have further demonstrated that selectivity for insertion of dNMPs into DNA rather than rNMPs varies from 10-fold to >10 6 -fold, depending on the DNA polymerase and the dNTP/rNTP pair examined. rNMP incorporation during DNA synthesis is potentially made more probable by the fact that the concentrations of rNTPs in vivo are higher than are the concentrations of dNTPs (e.g., see refs.…”
mentioning
confidence: 99%
“…However, pol differs from pol and pol ␤ in that it lacks dRP lyase activity (10) but relatively efficiently incorporates rNTPs into DNA (15,16). Recent evidence suggests that pol , but not pol , can fill short gaps in DNA during NHEJ even when 3Ј termini lack one or two complementary bases in the template strand.…”
mentioning
confidence: 99%